Sistem Pendidikan Jepang dan Amerika Serikat - Okta Viani; Leppe Firmansyah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the education systems of Japan and the United States with the aim of identifying their main characteristics, strengths, and weaknesses in addressing global challenges. The Japanese education system emphasizes discipline, cooperation, and character building as the foundation for academic achievement and moral development. Meanwhile, the American education system prioritizes creativity, freedom of expression, and an individual-centered approach that encourages critical thinking and innovation. The comparison reveals fundamental differences in educational philosophy and classroom practices, particularly in curriculum design, teacher-student interaction, and assessment methods. Despite these differences, both systems share a common vision of preparing competent and adaptable generations capable of contributing to the global society. The findings of this study are expected to provide valuable insights for the development of Indonesia’s education system, especially in formulating policies that combine Japan’s strong character-based education and the United States’ innovation-oriented learning. By integrating these strengths, Indonesia can create a more holistic and globally competitive education framework suitable for the 21st century.